2017
DOI: 10.17235/reed.2017.4902/2017
|View full text |Cite
|
Sign up to set email alerts
|

Is cholecystectomy the treatment of choice for acute acalculous cholecystitis? A systematic review of the literature

Abstract: Percutaneous cholecystostomy may be the first treatment option for patients with acute acalculous cholecystitis except in cases with a perforation or gallbladder gangrene. Patients at low surgical risk may benefit from cholecystectomy but both treatment options may be effective. Percutaneous cholecystostomy in patients with acute acalculous cholecystitis may be a definitive therapy with no need for a subsequent elective cholecystectomy. However, the overall quality of studies is low and the final recommendatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 26 publications
0
15
0
1
Order By: Relevance
“…Long‐term follow‐up monitoring, which was performed in our patients, also confirmed these observations. The observation seems to be very important for surgeons who make determinations about cholecystectomy in children with EBV …”
Section: Discussionmentioning
confidence: 98%
“…Long‐term follow‐up monitoring, which was performed in our patients, also confirmed these observations. The observation seems to be very important for surgeons who make determinations about cholecystectomy in children with EBV …”
Section: Discussionmentioning
confidence: 98%
“…There are studies suggesting that PC may be a definitive therapy for acute acalculous cholecystitis with no need for subsequent elective cholecystectomy 17 . It appears safe to avoid interval cholecystectomy in patients who recover from acalculous cholecystitis, as they are typically highrisk surgical candidates 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Our overall mortality figures are significantly better compared to the similar studies published in the literature (13). In a systematic review on treatment of choice for ACC, Soria et al observed that mortality among patients with ACC is 30%, and it is related to clinical severity and higher prevalence of gangrene (50%) and perforation (10%) (14). In our series, mortality was significantly higher in patients with ACC compared to AC, which we think is mainly due to underlying associated co-morbidities.…”
Section: Discussionmentioning
confidence: 99%